Chapter Introduction publics and their health - historical problems and perspectives - Mold, Alex (Manchester University Press, 2023)
In this Introduction, we begin by examining the nature of 'the public' and 'public health' and how these changed over time. We then set out the key cross-cutting themes that this book will address before going on to summarise the contents of the chapters. We also reflect on what we think this book adds to our understanding of publics and their health. The COVID-19 pandemic has thrown the relationship between public health authorities and their publics into sharp relief. In order to prevent the spread of the virus, public health authorities in many countries exercised powers to severely curtail individual liberties. The public was also called upon to behave 'responsibly', whether that meant washing their hands, staying at home or wearing a face mask. Public health experts became public figures, as members of the public hungrily sought out data, advice and reassurance. The publicness of public health came under a renewed degree of scrutiny and debate.